Transcriptional Regulation of Drug Metabolizing CYP Enzymes by Proinflammatory Wnt5A Signaling in Human Coronary Artery Endothelial Cells - Skaria, Tom; Bachli, Esther; Schoedon, Gabriele (Frontiers in Pharmacology, 2021)
Downregulation of drug metabolizing enzymes and transporters by proinflammatory mediators in hepatocytes, enterocytes and renal tubular epithelium is an established mechanism affecting pharmacokinetics. Emerging evidences indicate that vascular endothelial cell expression of drug metabolizing enzymes and transporters may regulate pharmacokinetic pathways in heart to modulate local drug bioavailability and toxicity. However, whether inflammation regulates pharmacokinetic pathways in human cardiac vascular endothelial cells remains largely unknown. The lipid modified protein Wnt5A is emerging as a critical mediator of proinflammatory responses and disease severity in sepsis, hypertension and COVID-19. In the present study, we employed transcriptome profiling and gene ontology analyses to investigate the regulation of expression of drug metabolizing enzymes and transporters by Wnt5A in human coronary artery endothelial cells. Our study shows for the first time that Wnt5A induces the gene expression of CYP1A1 and CYP1B1 enzymes involved in phase I metabolism of a broad spectrum of drugs including chloroquine (the controversial drug for COVID-19) that is known to cause toxicity in myocardium. Further, the upregulation of CYP1A1 and CYP1B1 expression is preserved even during inflammatory crosstalk between Wnt5A and the prototypic proinflammatory IL-1β in human coronary artery endothelial cells. These findings stimulate further studies to test the critical roles of vascular endothelial cell CYP1A1 and CYP1B1, and the potential of vascular-targeted therapy with CYP1A1/CYP1B1 inhibitors in modulating myocardial pharmacokinetics in Wnt5A-associated inflammatory and cardiovascular diseases.